Characteristics of Plastic Pollution in the Environment: A Review - Li, Penghui; Wang, Xiaodan; Su, Min; Zou, Xiaoyan; Duan, Linlin; Zhang, Hongwu (Bulletin of environmental contamination and toxicology, 2021)
Plastics are ubiquitous in the environment and have become a hot topic in academic circles. Extensive studies have focused on analytical methods, source, abundance, transport, fate, degradation of plastics in the environment and threats to natural surroundings, wildlife or even human health. However, characteristics of plastic pollution, which are critical to understand this emerging problem, remain unknown up to now. Here, this paper reviews the major characteristics of plastic pollution in the environment to enhance present understanding of this issue. These characteristics, including diversity, persistence, global issues, combined pollution and threats to organisms and human health, are critically summarized in this work. Further, “plastic cycle” in the environment, namely, aquatic, atmospheric, and terrestrial system, is also discussed in this review. Finally, we highlight current challenges of plastic pollution posed to the public and also recommend the research trends in future work.